Meningkatkan Motivasi dan Hasil Belajar Mata Pelajaran PAI Materi Shalat Kewajibanku dengan Menggunakan Model Pembelajaran Discovery Learning di SDN 02 Padang Kejai - Yusdayenti, Yusdayenti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to explore the implementation of the Project-Based Learning (PBL) model in Islamic Religious Education (PAI) at SD Negeri 18 Tanjung Gadang. This research uses a classroom action research approach, which is carried out in two cycles, focusing on improving students’ skills in understanding and applying PAI concepts. The results show that in the first cycle, although there was improvement, time management and material comprehension were still challenges. However, in the second cycle, after improvements were made, significant progress was achieved, with more students actively participating and applying the material better. This study concludes that PBL is effective in enhancing students’ skills in understanding the material and developing their collaborative and critical thinking skills.